1995
DOI: 10.1007/bf01384313
|View full text |Cite
|
Sign up to set email alerts
|

Property preserving abstractions for the verification of concurrent systems

Abstract: Abstract. We study property preserving transformations for reactive systems. The main idea is the use of simulationsparameterized by Galois connections( ), relating the lattices of properties of two systems. We propose and study a notion of preservation of properties expressed by formulas of a logic, by a function mapping sets of states of a system S into sets of states of a system S'. We g i v e results on the preservation of properties expressed in sublanguages of the branching time -calculus when two system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
165
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(167 citation statements)
references
References 25 publications
0
165
0
2
Order By: Relevance
“…Loiseaux, et al [22], proved that all P-properties true of an over-approximating transition relation are preserved in the corresponding concrete transition relation and that when one over-approximating transition relation is more precise than another, then the first preserves all the P-properties of the second. Dams extended this result to under-approximations and Q-properties and proved that his definitions of R best and R best possess the most PQ-propositions of any sound, mixed transition system.…”
Section: Validation and Refutation Logicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loiseaux, et al [22], proved that all P-properties true of an over-approximating transition relation are preserved in the corresponding concrete transition relation and that when one over-approximating transition relation is more precise than another, then the first preserves all the P-properties of the second. Dams extended this result to under-approximations and Q-properties and proved that his definitions of R best and R best possess the most PQ-propositions of any sound, mixed transition system.…”
Section: Validation and Refutation Logicsmentioning
confidence: 99%
“…In addition to Dams's work [10,11], three other lines of research deserve mention: Loiseaux, et al [22] showed an equivalence between simulations and Galois connections: For sets C and A, and ρ ⊆ C × A, they note that P(C) post[ρ],p re[ρ] P(A) is always a Galois connection. 18 For R ⊆ C × C and R ⊆ A × A, simulation is equivalently defined as R is ρ-simulated by R iff R −1 · ρ ⊆ ρ · (R ) −1 Treating R −1 and (R ) −1 as functions, we can define Galois-connection soundness as (R ) −1 is a sound over-approximation for R −1 with respect to γ iff…”
Section: Related Workmentioning
confidence: 99%
“…Given a description function ρ : S → S α , the functions α = post(ρ) and γ = pre(ρ) form a Galois connection from 2 S to 2 S α (Proposition 6 of [19]); post and pre are the corresponding post-and preimage relations.…”
Section: Timer Abstraction and Fairnessmentioning
confidence: 99%
“…2L + µ (i.e. formulas of the µ-calculus without negation and containing only the 2 operator) or LTL [19,11].…”
Section: Timer Abstraction and Fairnessmentioning
confidence: 99%
See 1 more Smart Citation